2011
DOI: 10.13031/2013.39824
|View full text |Cite
|
Sign up to set email alerts
|

Determining Radio Frequency Heating Uniformity of Mixed Beans for Disinfestation Treatments

Abstract: Chickpeas and lentils are two important legumes grown in the U.S. that need phytosanitary treatments before export to several countries, but it is difficult to artificially infest them with live cowpea weevil for radio frequency (RF) treatment validation. To evaluate the more readily infested black-eyed peas and mung beans as surrogates for chickpeas and lentils, the thermal and dielectric properties of black-eyed peas and mung beans at selected moisture contents were measured and compared with those of chickp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…To meet phytosanitary and quarantine regulations for international trade, there is an urgent need in developing nonchemical postharvest pest control methods for dry soybeans. Radio frequency (RF) energy is an electromagnetic wave with a frequency of 1e300 MHz, which provides rapid and volumetric heating, and has been studied as a non-chemical alternative for postharvest insect control in dry products (Halverson, Burkholder, Bigelow, Nordheim, & Misenheimer, 1996;Nelson, 1973;Tang, Ikediala, Wang, Hansen, & Cavalieri, 2000), such as alfalfa seed (Yang, Zhao, & Wells, 2003), grain (Nelson, 1996), legume (Jiao, Tang, Johnson, Tiwari, & Wang, 2011;Wang, Tiwari, Jiao, Johnson, & Tang, 2010), lentil (Jiao, Johnson, Tang, & Wang, 2012), rice (Lagunas-Solar et al, 2007;Zhao, Qiu, Xiong, & Cheng, 2007), walnut (Mitcham et al, 2004;Wang et al, 2001;Wang, Monzon, Johnson, Mitcham, & Tang, 2007a, b;Wang et al, 2006), and wheat (Halverson et al, 1996). The relatively long wavelength of RF usually results in deep penetration depth and predictable temperature profiles in foods, but the nonuniform heating is still a problem for RF heating technology to be applicable in the food industry (Tang et al, 2000;Wang et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…To meet phytosanitary and quarantine regulations for international trade, there is an urgent need in developing nonchemical postharvest pest control methods for dry soybeans. Radio frequency (RF) energy is an electromagnetic wave with a frequency of 1e300 MHz, which provides rapid and volumetric heating, and has been studied as a non-chemical alternative for postharvest insect control in dry products (Halverson, Burkholder, Bigelow, Nordheim, & Misenheimer, 1996;Nelson, 1973;Tang, Ikediala, Wang, Hansen, & Cavalieri, 2000), such as alfalfa seed (Yang, Zhao, & Wells, 2003), grain (Nelson, 1996), legume (Jiao, Tang, Johnson, Tiwari, & Wang, 2011;Wang, Tiwari, Jiao, Johnson, & Tang, 2010), lentil (Jiao, Johnson, Tang, & Wang, 2012), rice (Lagunas-Solar et al, 2007;Zhao, Qiu, Xiong, & Cheng, 2007), walnut (Mitcham et al, 2004;Wang et al, 2001;Wang, Monzon, Johnson, Mitcham, & Tang, 2007a, b;Wang et al, 2006), and wheat (Halverson et al, 1996). The relatively long wavelength of RF usually results in deep penetration depth and predictable temperature profiles in foods, but the nonuniform heating is still a problem for RF heating technology to be applicable in the food industry (Tang et al, 2000;Wang et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…These measurements were made in a wide range of moisture content, temperature and at density equivalent to density of respective cereal grain; so as the determined data can be applied to corresponding grains/cereals for various applications particularly for postharvest pest control (Nelson and Whitney, 1960;Nelson, 1976;Wang et al, 2003a;Jiao et al, 2011;Shrestha and Baik, 2013). There is also a dire need to develop such applicators for cereal grain flours.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RF treatments have been developed to control codling moth (Wang et al, 2001) and navel orangeworm (Wang et al, 2002(Wang et al, , 2007a(Wang et al, , 2007bMitcham et al, 2004;Gao et al, 2010) in in-shell walnuts and almonds. Available research results on RF heating for low-moisture products Jiao et al, 2011aJiao et al, , 2011b) have shown its potential as an environmentally friendly pest-control method in coffee beans.…”
mentioning
confidence: 99%